The Social and Intellectual History of Santri In Indonesia - Tsabit Azinar Ahmad (ADP Publisher, 2023)
This research explores the social and intellectual history of Santri in Indonesia as an integral part of the country’s religious and cultural life. This research seeks to reveal the role of Santri in shaping the social dynamics of society, as well as to understand their intellectual contributions to social change in Indonesia from pre-independence to the present day. The research method involves the analysis of historical documents and literature studies to compile a comprehensive narrative of the social and intellectual journey of santri. In this context, the role of the santri, the madrasah, and the pesantren as traditional centers of education that play a vital role in the spread of Islam and the formation of the santri character is analyzed. This research shows that Santri has a dual role as an agent of social and intellectual transformation. The findings of this study are expected to provide in-depth insights into the dynamics of santri in social and intellectual aspects, their role in social change, and the intellectual impact that has been generated. Along with the times, understanding the social and intellectual history of Santri is expected to contribute positively to Indonesian society’s understanding of cultural and religious diversity.